2022
DOI: 10.3389/fonc.2022.872225
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Aumolertinib as Neoadjuvant Therapy for Patients With Unresectable Stage III Non-Small Cell Lung Cancer With Activated EGFR Mutation: Case Series

Abstract: BackgroundThere is no standard treatment for stage III lung cancer due to its low surgical resection rate, and improving PFS and survival of patients with III NSCLC has become an urgent challenge in clinical treatment. For EGFR mutation-positive patients, targeted therapy has the remarkable feature of high efficiency and low toxicity compared with first-line standard chemotherapy, and targeted neoadjuvant therapy needs to be further explored.MethodWe report 3 diagnosed cases of locally advanced unresectable NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Likewise, the EMERGING-CTONG 1103 study (25) revealed that there is a tendency toward an improved overall response rate, lymph node step-down, major pathological response and R0 resection rate with the neoadjuvant erlotinib, in comparison with a neoadjuvant chemotherapy for patients who suffered from EGFRm NSCLC and chronic progression-free survival to a great extent. According to the indications from case reports and other reported clinical tests, EGFR-tyrosine kinase inhibitor (EGFR-TKI) therapy before surgery can achieve a certain effect for patients with resectable NSCLC (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), which indicates that neoadjuvant targeted therapy can also become a clinical option. Based on superior sulcus tumors exhibiting the same biological behavior as other lung cancers (37), we consider that neoadjuvant targeted therapy may be a consideration for superior sulcus tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the EMERGING-CTONG 1103 study (25) revealed that there is a tendency toward an improved overall response rate, lymph node step-down, major pathological response and R0 resection rate with the neoadjuvant erlotinib, in comparison with a neoadjuvant chemotherapy for patients who suffered from EGFRm NSCLC and chronic progression-free survival to a great extent. According to the indications from case reports and other reported clinical tests, EGFR-tyrosine kinase inhibitor (EGFR-TKI) therapy before surgery can achieve a certain effect for patients with resectable NSCLC (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), which indicates that neoadjuvant targeted therapy can also become a clinical option. Based on superior sulcus tumors exhibiting the same biological behavior as other lung cancers (37), we consider that neoadjuvant targeted therapy may be a consideration for superior sulcus tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Aumolertinib operates by inhibiting the activity of EGFR whose aberration causes cancers. [195][196][197][198][199][200][201] Savolitinib, designed as a small molecule inhibitor targeting the tyrosine kinase of the mesenchymal epithelial transition factor (MET), is mainly intended for treating non-small cell lung cancer (NSCLC) associated with MET mutations. Functioning as a MET tyrosine kinase inhibitor with high specificity, it exhibits promise in treating various cancers, such as NSCLC, breast, head and neck, colorectal, gastric, pancreatic, and other gastrointestinal cancers.…”
Section: -110mentioning
confidence: 99%
“…This result may be highly related to the inhibitory nature of EGFR-TKIs’ anti-tumor mechanism and spatial heterogeneity within the tumor. Feng et al (2022) recently reported 3 cases of EGFR-mutant stage III unresectable NSCLC who initially received 1-2 cycles of neoadjuvant chemotherapy but were replaced with 2 cycles of neoadjuvant aumolertinib therapy due to poor therapeutic efficacy or intolerance of chemotherapy. Interestingly, two of these patients obtained MPR and another one obtained pCR.…”
Section: Future Considerations Of Research On the Neoadjuvant Targete...mentioning
confidence: 99%